Tracing Back the Issue of Speaking Anxiety among EFL Learners: From Possible Causes to Practical Implications - Yogi Saputra Mahmud (Journal of English Language Studies, 2018)
Through the exploration of related empirical studies in the field, this essay aims to scrutinize the possible causes of speaking anxiety issue among EFL learners and the critical implications to alleviate the issue. Although several studies have discussed the causes of speaking anxiety, those studies do not emphasize the interrelationship between each cause. Hence, this paper attempts to enrich the related field by tracing back the interconnected relationship between the causes of speaking anxiety, including the new ways to address this adverse issue. The possible causes of speaking anxiety in the EFL classrooms are further classified into two primary causes, including the affective-related and linguistic-related causes. The promotion of cooperative learning atmosphere and the needs to rebalance the focus of achieving linguistic accuracy and providing broad speaking opportunities are the critical solutions to cope with the issue. The implications can be essential references for both the EFL teachers and learners in the classroom.